Implementasi Kebijakan Revitalisasi Pendidikan Menengah Kejuruan Di Provinsi Jawa Timur - Maharani, Wydha Mustika; Wati, Dian Marta (Universitas 17 Agustus 1945 Surabaya, 2022)
Central government's attention to the quality of SMK graduates is increasingly visible, as evidenced by the issuance of Presidential Instruction Number 9 of 2016 concerning Vocational Education Revitalization. The revitalization of vocational education is very important given the rapid development of technology. It takes vocational graduates who have skills in a field and have a global perspective so that the employment of vocational graduates continues to increase. Revitalization supports industrial development clusters so that the implementation of revitalization also adapts to existing clusters in each region so that vocational education can contribute directly and be able to optimize the potential that exists in each region. In 2020, the Central Government has changed the paradigm of vocational education programs that were previously supply driven to demand driven, from a centralized management system to a decentralized one, from a learning approach to a competency subject approach. based on learning (CBT) and from learning patterns using a subject approach. The implementation of highly structured vocational education becomes more flexible and permeable. Based on the expectations, potentials, regulations and theories that underlie the problems of vocational secondary education, the formulation of this research concerns the issue of how to implement the revitalization policy of vocational secondary education, especially in East Java Province? This study used descriptive qualitative method. In determining the sample area, it was determined by purposive sampling by taking several vocational schools according to the superior potential in East Java Province. Keywords: Policy Implementation, Revitalization, Vocational High Schools